2012
DOI: 10.1007/s10509-012-1247-7
|View full text |Cite
|
Sign up to set email alerts
|

Fast magnetoacoustic solitary waves in dense magnetoplasmas in a cylindrical geometry

Abstract: Nonlinear properties of the quantum magnetoacoustic wave are studied in electron-ion magnetoplasmas. In this regard, cylindrical Korteweg deVries (CKdV) equation is derived for small amplitude perturbations. The solution of the planar KdV equation is obtained using the tanh method and is subsequently used as an initial profile to solve the CKdV equation. It is found that the system under consideration admits compressive solitary structures. Finally, it is found that the amplitude as well as the width of the no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…It can be observed that increasing the spin effects reduces the phase speed as can also be seen from the dispersion relation given by equation (19). Thus, the linear dispersion relation reduces well to the one obtained without spin effects earlier for relevant model [53]. It is clearly shown in the plot that spin parameter modifies the phase speeds differently in the two limits ε 0 <1 and ε 0 >1.…”
supporting
confidence: 74%
“…It can be observed that increasing the spin effects reduces the phase speed as can also be seen from the dispersion relation given by equation (19). Thus, the linear dispersion relation reduces well to the one obtained without spin effects earlier for relevant model [53]. It is clearly shown in the plot that spin parameter modifies the phase speeds differently in the two limits ε 0 <1 and ε 0 >1.…”
supporting
confidence: 74%
“…Magnetoacoustic wave is a fundamental mode in magnetized plasma which propagates in the perpendicular direction of external magnetic field, and both density and magnetic field compression are responsible for the propagation of magnetoacoustic wave (Miller and Wiita 1986). Many authors have investigated magnetoacoustic solitary waves' (MASWs) nonlinear structures in recent years Mahmood 2011a,b, 2012;Liu et al 2011;Valiulina and Dubinov 2012;Masood et al 2013;Ruan et al 2013). However, to the best of our knowledge, the propagation of MASWs in PI plasmas has not been investigated so far.…”
Section: Introductionmentioning
confidence: 99%